DAYA ANTIMIKROBA SARI AKAR MAMBU (Millettia cericea W. & A.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DAN Salmonella typhi - Sarip, Mhd.; Amri, Erismar; Fitriani, Vivi (Pendidikan Biologi, 2014)
ABSTRACTÂ Mambu root (Millettia cericea W. & A. ) is a kind of plant that suppose has a role as antimicrobial that able to pursuing growth of Escherichia coli and Salmonella typhi bacterias. It is caused by the containing of Mambu root that compound on flavonoid, alkaloid, and saponin. The purpose of this researcher is to know the influence of essence in Mambu root to growth of Escherichia coli and Salmonella typhi bacterias, and also to know the concentration of essence in Mambu root that can pursuing growth of Escherichia coli and Salmonella typhi bacterias. This reseacher have been done in January until February 2014 at Laboratorium Kopertis Wilayah X, Padang. The scheme/outline of this experiment is RAL with 12 of treatment and 3 times repetition. The concentrate of essence in Mambu root that have used for each bacterias is same, they are 10%,20%, 30%, 40%, 50% and amoksisilin 10% (positive control). The result of the data has been analyzed with sidik ragam analisys (ANOVA) and DNMRT tests. The result of this research showing that essence of Mambu root (Millettia cericea W. & A. ) Â can inhibit growth Escherichia coli and Salmonella typhi bacterias. The concentrate of essence in Mambu root that effective can inhibit the growth Escherichia coli and Salmonella typhi bacterias, that is to 50% concentrate. The mean inhibition zone for Escherichia coli bacterias is 11,53 mm while the mean inhibition zone for Salmonella typhi bacterias is 7,57 mm.